2022
DOI: 10.1002/pat.5671
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation for chlorinated butyl rubber composite reinforced by dendritic amino‐terminated aromatic polyamide

Abstract: In this study, we explore the application of dendrimers in damping modification of chlorinated butyl rubber (CIIR) through molecular dynamics simulation. The dendrimer is dendritic polyamide G2 with polar end groups. The results showed that the composite with 9‐equivalent of G2 exhibited significant damping characteristics. The small difference of solubility indicates that G2 had good compatibility with CIIR. The cohesive energy density and bonding energy are improved. Under the same external force, the hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Xia[18] controlled the damping properties of IIR by varying the chain length and content of PIB with damping temperature range up to 115.4°C and peak tanδ of 2.01. The introduction of a larger volume and a certain number of side groups to the molecular structure of rubber utilizing polymerization [19], [20] is an important method to improve the damping properties of rubber. However, the modi cation reaction is more complex and di cult to control precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Xia[18] controlled the damping properties of IIR by varying the chain length and content of PIB with damping temperature range up to 115.4°C and peak tanδ of 2.01. The introduction of a larger volume and a certain number of side groups to the molecular structure of rubber utilizing polymerization [19], [20] is an important method to improve the damping properties of rubber. However, the modi cation reaction is more complex and di cult to control precisely.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations can provide insightful information on the atomic scale, making it difficult to provide experimental methods 25 . On the other hand, MD refers to the study of microscopic phenomena from a molecular or atomic point of view, so as to predict or explain macroscopic phenomena from a microscopic point of view and we can predict whether a molecule is suitable for improving a particular performance 26,27 . Li et al 28 further discussed the compatibility between an asphalt matrix and a styrene‐butadiene‐styrene (SBS) modifier using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…25 On the other hand, MD refers to the study of microscopic phenomena from a molecular or atomic point of view, so as to predict or explain macroscopic phenomena from a microscopic point of view and we can predict whether a molecule is suitable for improving a particular performance. 26,27 Li et al 28 further discussed the compatibility between an asphalt matrix and a styrene-butadienestyrene (SBS) modifier using MD simulations. The simulation results showed that the interaction between SBS modifier and asphalt matrix improved their compatibility, and the van der Waals potential energy was dominant in the intermolecular potential energy.…”
Section: Introductionmentioning
confidence: 99%